Wildlife Diversity of Madhupur National Park, Bangladesh (Jahangirnagar University Journal of Biological Sciences, 2018)
The study was conducted to know the wildlife diversity of Madhupur National Park of Bangladesh from June 2014 to March 2015. A total of 151 species of wildlife (amphibians to mammals) belonging to 23 orders and 62 families were recorded which covers 16.41% of total wildlife species in our country. Among them 10 (7%) were amphibians, 15 (10%) reptiles, 111 (73%) birds and 15 (10%) mammals while 65 (43.05%) were very common, 41 (27.16%) common, 25 (16.55%) uncommon and 20 (13.24%) were rare. Among the 20 species of migratory birds, 15 (75%) were winter visitors and 5 (25%) summer visitors. The forests and other wildlife habitats in and around Madhupur National Park are decreasing rapidly due to illegal logging, land conversion for agriculture and human settlements.Jahangirnagar University J. Biol. Sci. 7(1): 1-13, 2018 (June)